Felix Cohen and the Spanish Moment in Federal Indian Law: A Study in Law, Politics and Historiography - Boast, Richard P (Victoria University of Wellington Law Review, 2008)
One of the best-known discussions of the historical foundations of native title law is Felix Cohen's famous paper on the Spanish Origins of Federal Indian Law, published originally in 1942 and since then reprinted many times. This article cites Cohen's paper in its political and historiographical context, paying particular attention to Cohen's role as one of the architects of the Indian Reorganisation Act of 1934, and considering also shifts in American historiography and legal writing relating to the Spanish legacy as exemplified by legal historians such as James Brown Scott and historians such as H E Bolton. This article also considers fully Cohen's analysis of the precise ways in which Spanish law penetrated the legal framework of Federal Indian Law in the United States and concludes that, as a historical discussion, Cohen's work is in need of substantial revision. In particular Cohen's arguments that Spanish law influenced federal Indian law via international law and by means of judicial consideration of old Spanish land claims seem difficult to sustain.